Hollyberry homicide - Farrow, Sharon (Farrow, Sharon. Berry Basket mystery., 2020)
When the set of Oriole Point's production of A Christmas Carol is plagued by strange accidents and then murder, Marlee Jacob, who is playing Jacob Marley, must find the culprit before it's curtains for someone else.